Relationship Of Gestational Age With Hyper Bilirubin Incidence In 3 Days Neonates At Dustira Cimahi Hospital - Oryza Tri Novita Oryza (Universitas Nahdlatul Ulama Surabaya, 2022)
One of the most typical clinical manifestations of the infant is hyperbilirubinemia. Jaundice sends more than 85% of term newborns back to the hospital within the first week of life. 60% of term newborns and 80% of preterm (less term) infants have hyperbilirubinemia. If hyper bilirubin is not appropriately treated, it can damage brain cells, cause seizures, and progress to kernicterus, even causing death. Even if the newborn gets kernicterus and recovers and can be passed, the baby can grow but not develop optimally and can even cause long-term effects such as mental impairment. This type of research is analytical research. This study was an observational study that related two variables: namely, the relationship between gestational age and the incidence of hyperbilirubinemia in neonates aged three days. The type of approach in this research is cross-sectional. Sampling was done using a purposive sampling technique with as many as 286 samples. The median gestational age for neonates with hyperbilirubinemia at Dustira Cimahi Hospital in 2021 was 36 weeks, still considered preterm, with a minimum gestational age of 30 weeks and a maximum of 43 weeks. The median bilirubin level in neonates with hyperbilirubinemia at Dustira Cimahi Hospital in 2021 was 10 mg/dL which was still classified as physiological hyper bilirubin, with a minimum level of 5.52 mg/dL and a maximum level of 16.03 mg/dL. There was a significant relationship between gestational age and the incidence of hyperbilirubinemia in neonates aged 3 days at Dustira Cimahi Hospital in 2021 with moderate strength and negative correlation direction.